Synthesis of Aryl Dithiocarbamates from Tetramethylthiuram Monosulfide (TMTM) and Aryl Boronic Acids: Copper-Catalyzed Construction of C(sp2)–S Bonds - Xia, Xu-Ling; Zhu, Qi-Long; Chen, Jin-Quan; Shi, Zhen; Dong, Zhi-Bing (Synthesis, 2021)
A highly efficient method for the synthesis of S-aryl dithiocarbamates is reported. By using tetramethylthiuram monosulfide (TMTM) and aryl boronic acids as starting materials, C(sp2)–S bond-forming reactions proceed smoothly to give the desired aryl dithiocarbamates in good to excellent yields. The methodology features a simple procedure, broad functional group tolerance and excellent yields, whilst showing potential synthetic value for the preparation of a diverse range of biologically and pharmaceutically active compounds.
Keywords: dithiocarbamates; tetramethylthiuram monosulfide; boronic acids; organosulfur; copper